2017
DOI: 10.22214/ijraset.2017.9238
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Soil Nematode Diversity in Relation to the Soil Parameters from Sugarcane Fields of Aurangabad District Maharashtra State, India

Abstract: A survey was conducted from sugarcane fields at four completely different sampling sites like Paithan, Aurangabad, Phulambri and Khultabad taluka. During May-2016 -April-2017. To study the nematodes diversity and their correlation with the soil parameters soil samples was collected from the sugarcane root zones from the four completely different sugarcane fields. The Nematodes were extracted from collected soil samples by the Baermann's funnel technique. And also prepared the soil samples for testing the diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Phytonematodes as the cause of plant diseases are widely reported in almost all sugarcane growing countries [5]. Phytonematodes in sugarcane have been widely reported in several other countries, including China [6], South Africa [7], India [8], Nigeria [4], Japan [9], and Brazil [10]. In Indonesia, the initial study of phytonematodes in sugarcane was first reported in 1976-1978 in seven sugar mill areas in East Java [11].…”
Section: Introductionmentioning
confidence: 99%
“…Phytonematodes as the cause of plant diseases are widely reported in almost all sugarcane growing countries [5]. Phytonematodes in sugarcane have been widely reported in several other countries, including China [6], South Africa [7], India [8], Nigeria [4], Japan [9], and Brazil [10]. In Indonesia, the initial study of phytonematodes in sugarcane was first reported in 1976-1978 in seven sugar mill areas in East Java [11].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a positive correlation was found between temperature and electrical conductivity and nematode diversity. Finally, a negative correlation was found between soil moisture and pH and the proportion of nematodes, but no correlation was found between soil moisture content and nematode diversity (Gade and Hiware, 2017). In a study that investigated the infection of pineapple by Pratylenchus brachyurus, Sarah et al (1991) found a negative relationship between nematode population densities and soil pH.…”
mentioning
confidence: 99%